2020
DOI: 10.31002/metathesis.v4i2.2784
|View full text |Cite
|
Sign up to set email alerts
|

Developing HOTS-Based Critical Reading Textbook for Junior High Schools in Ngabang

Abstract: This study is a research and development under the issue of developing English textbook oriented to HOTS-Based Critical thinking for Junior High School Students especially for the seventh grade students in Ngabang, Landak, West Kalimantan. It is based on the evidence that the English teachers find difficulty in finding HOTS-based English textbook as one of the teaching tools. This issue is supported by the result of textbook evaluation. It reveals that most of the existing English textbooks used by the teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The learning was still oriented to lower order thinking skills (LOTS) (Aisah et al, 2021;Kurnia Atiullah et al, 2019). It also said that designing the product in term of blueprint was the best way before developing the product, it was a great guideline for the researcher to create the supplementary book product (Surtikanti et al, 2020;Torlakson & Bonilla, 2014). In the development stage also found that the researcher already finished the stage and focus on the students' activities, students learning objectives, syllabus used, book design and illustration that were really important for the accordance learning and improve students learning motivation based on the real-life situation, as the previous study (Anggraini et al, 2020;Margana & Widyantoro, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The learning was still oriented to lower order thinking skills (LOTS) (Aisah et al, 2021;Kurnia Atiullah et al, 2019). It also said that designing the product in term of blueprint was the best way before developing the product, it was a great guideline for the researcher to create the supplementary book product (Surtikanti et al, 2020;Torlakson & Bonilla, 2014). In the development stage also found that the researcher already finished the stage and focus on the students' activities, students learning objectives, syllabus used, book design and illustration that were really important for the accordance learning and improve students learning motivation based on the real-life situation, as the previous study (Anggraini et al, 2020;Margana & Widyantoro, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed introducing English at the primary stage, copying the English language in the classroom and daily lives, emphasizing vocabulary size and its development, applying the theme as the topic, and providing a variety of instruments in teaching can help to engage students to use English every day. Hence, the present research is also in line with the need analysis, which was employed by (Surtikanti, (2019). The research and development (R & D) were aimed to develop learning materials by conducting preliminary survey, designing and developing the prototype of the product, conducting limited testing and product validation, having a revision process, and describing the research result.…”
Section: Introductionmentioning
confidence: 97%
“…Providing students with reading-related activities in textbooks is not enough to ensure that students are involved with the reading process, especially in online learning (Ayu & Indrawati, 2019;Efriana, 2021;Margana & Widyantoro, 2017). Therefore, teachers can use reading texts in textbooks into the learning process as one of the best ways to do it (Sucipto & Cahyo, 2019;Surtikanti et al, 2020;Tayyeh et al, 2021). Text exploitation is the teacher's strategy or way of utilizing reading texts in reading activities in the classroom.…”
Section: Introductionmentioning
confidence: 99%